Effect of impellers on particle mixing behaviour in KR desulphurization process. (7th February 2022) - Ji, Junhong; Du, Hongxian; Jiang, Yu; Li, Deqiang; Zhang, Sitong
ABSTRACT: Three types of impellers are developed to improve reagent efficiency in the desulfurization process of hot metal by kanbara reactor stirring method. The movement and dispersion behavior of particles are investigated using the CFD technology. The flow structure, particle volume fraction distribution and mixing time are taken as the characteristics to describe the entrainment ability and mixing ability of the impellers. The results show that the square center impeller (impeller B) improves the flow structure of the molten iron, and makes the volume fraction distribution of the particles much better than that of the traditional impeller (impeller A), the mixing time is the shortest among the three impellers under the same operating parameters. The blades with downward angle (impeller C and impeller D) improve the mixing effect of the region below the impeller, and the impeller C is more sensitive to the change of rotation speed.